Temperature and deaths from ischaemic heart disease. Issue 1 (March 1977) - Bainton, D; Moore, F; Sweetnam, P
Abstract : Certain features of the relationship between 11 measurements of weekly temperature and the number of deaths from ischaemic heart disease (IHD) within age groups in Greater London between 1970 and 1974 are described. Firstly, the correlation coefficients between age-specific deaths from IHD and each of the temperature variables are of a similar order. Secondly, in contrast, the linear regression coefficients between deaths and temperature are more variable and depend upon the particular measurement of temperature chosen. Thirdly, the proportional changes in the number of deaths with the temperature variables are similar within specific age groups; consequently it is suggested that deaths from IHD and temperature may be directly related.